Why did they not borrow? Debt-averse farmers in rural Vietnam - Trinh, Khoa A. et al (The Developing Economics)
Nonborrowers are defined as debt averse if they have never borrowed in the past and prefer avoiding debt in the future, even when offered generous borrowing terms such as zero interest rates, zero collateral, and easy debt-forgiveness. Other nonborrower types have either borrowed in the past or are open to doing so in the future. To better understand nonborrowing behavior, credit preference types (CPTs) were measured among 575 low-income farmers in Mekong Delta, Vietnam. Among 208 current nonborrowers, 156 had never borrowed and only seven were credit rationed. Among never-borrowers, 102 were debt-averse. Thus, more than half of eligible nonborrowers (102 out of 201) were debt averse. This high prevalence challenges the assumption of unmet credit demand among the poor. Disaggregating CPTs reveals heterogeneity among nonborrowers that would remain observationally equivalent otherwise. We report reasons for not borrowing and investigate how observable characteristics influence the likelihood of debt aversion.- Reproduced
Keywords: Nonborrower, Nonborrowing, Behavior, Debt aversion, Reasons for homewing, Credit preference types